The Imposition of a Niet Ontvankelijke Verklaard Verdict in Cases of Domestic Violence in Military Courts - Ilma Azzahra Kurniawan; Slamet Tri Wahyudi; Supardi Supardi (International Journal of Sociology and Law, 2025)
The purpose of writing this thesis is to find out about the Judge's considerations in issuing a Niet Ontvankelijk Verklaard (NO) verdict on domestic violence cases in military courts and to find out how the verdict should be issued on domestic violence cases in military courts. The type of research used is normative legal research because in this study the author focuses on the inconsistency between the expected conditions that have been regulated in the law and the reality that actually occurs, where this study uses a legislative approach, a case approach, and a conceptual approach. The conclusion of this study is that the Judge's consideration in issuing a Niet Ontvankelijk Verklaard (NO) verdict on domestic violence cases in military courts is because the victim has withdrawn her complaint before the main case examination, even though the withdrawal of the complaint violates Article 75 of the Criminal Code, the Judge still grants the request because the Judge uses the Supreme Court Decision Number 2238 K / Pid.Sus / 2013 dated March 5, 2014 and the Supreme Court Decision Number 1600-K / Pid / 2009 and the Judge prioritizes the value of justice in resolving the case and uses the principles of fast, simple, and low-cost justice. Because the Niet Ontvankelijk Verklaard (NO) verdict is not known in criminal cases, in the author's opinion, ideally the Judge should issue a suspended sentence because the type of suspended sentence is also a type of punishment and is not at all an acquittal or deletion, while the existence of a probationary period that has been determined by the Judge aims to educate the perpetrator to be more careful and able to improve themselves